STRICT LIABILITY ATAS PERBUATAN MELAWAN HUKUM DITINJAU DARI FILSAFAT HUKUM - Septian Fujiansyah (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
Abstract The concept of unlawful acts (PMH) in the Civil Code does not explicitly describe the phrase regarding PMH. It is known that if you look at the contents of the provisions of Article 1365 of the Civil Code, it can be seen that the article does not provide a formulation regarding unlawful acts, but only regulates how a person suffers losses due to an unlawful act. unlawful acts committed by other people can file a lawsuit against him. compensation. For this reason, from a legal point of view, it is necessary to study the intent of the act which is included in the category of unlawful act, including its relation to the strict liability that can be applied to those who are proven to have committed an unlawful act. The purpose of this study is to find out the basic philosophical concept of unlawful acts in Indonesia, as well as to find out the strict liability that can be applied to perpetrators of unlawful acts. The research conducted was normative juridical research using secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the study, it is known that the philosophically basic concept of unlawful acts in Indonesia is based on the basis of Roman law, namely the principle of unlawful acts which are simple, but can capture all, in the form of unlawful acts. which is formulated as an act that harms other people, for which the person who was wronged must pay compensation, so that philosophically as long as it violates the law and harms other people it is included in the category of Unlawful Acts. Then the firm responsibilities that can be applied to perpetrators of unlawful acts in general are based on Article 1365 of the Civil Code, namely in the form of compensation, both principal compensation, interest and additional compensation, the category of legal responsibility is both material losses and compensation. non-material compensation. Keywords: Responsibility, Unlawful Acts, Legal Philosophy